Merleau-Ponty's phenomenology of language - Apostolopoulos, Dimitris (Rowman & Littlefield International, 2019)
Through accessible analyses of Merleau-Ponty's views of linguistic expression and understanding, and by tracing the evolution of these views throughout the course of his philosophical career, Merleau-Ponty's Phenomenology of Language offers a comprehensive picture of his engagement with the philosophy of language.